Morphology of endoskeleton and spination in the sea star Midgardia xandaros (Brisingida: Brisingidae) from the Gulf of Mexico - Esteban-Vázquez, Brenda-Lizbeth; De-los-Palos-Peña, Magdalena; Solís-Marín, Francisco-Alonso; Laguarda-Figueras, Alfredo (Revista de Biología Tropical, 2021)
Introduction. The deep-sea asteroid species of Brisingida have a nearly global distribution but have remained poorly understood due to their deep bathymetric distributions and fragile skeletons. Objective. To describe the external and internal morphology of Midgardia xandaros including the skeletal arrangement, through multifocal and SEM techniques. Methods. We examined a total of 21 specimens, including 27 arm fragments, from the Gulf of Mexico and Honduras. Two specimens were dissected. Results. Detailed descriptions of pedicellariae, abactinal, intercostal, inferomarginal, adambulacral, ambulacral, odontophore, and oral ossicles, and their spines are provided, emphasizing the articulations and muscle attachments. C-shaped valves pedicellariae and small pedicellariae valves with shorter denticulation areas were recognized. Conclusions. The morphological description of M. xandaros is expanded, providing the most extensive description of abactinal, first adambulacral, first and subsequent inferomarginal ossicles, abactinal spines, and C-shaped, crossed pedicellariae, as well as the distal arm plates, for a brisingid species using SEM to date.